Editorial Essay - Dark, Zachary; Butet-Roch, Laurence; Chan, Melvin; Petschke, Karl; Tanguay, Laura; Urquhart, Sarah (UnderCurrents: Journal of Critical Environmental Studies, 2025)
From the depths of Dante’s Inferno to Verne’s Twenty Thousand Leagues Under the Sea, subterranean and subaquatic environments have often been depicted as repositories of primordial forces and abiding secrets in the Western tradition. The much-repeated (if somewhat misleading; e.g., Copley, 2014) claim that humans have “explored” more of outer space than of Earth’s oceans points to the mystique associated with the deepest regions of this planet. Though dramatic environmental changes are becoming increasingly evident all across the face of the Earth, we surface-dwellers can scarcely fathom what has been occurring below the ground and beneath the waves. In these deep places, rising temperatures deplete aquifers and destabilize sea beds; infrastructures (both old and new) wind through vast urban undergrounds; heavy industry delves ever deeper in its search for fossil fuels, rare earth metals, and geothermal energy; and plastics and other toxic contaminants come to settle among the extremophiles inhabiting the most remote reaches of the ocean. [...]